Applicability of Generic Assays Based on Liquid Chromatography–Electrospray Mass Spectrometry to Study in vitro Metabolism of 55 Structurally Diverse Compounds - Rousu, Timo; Hokkanen, Juho; Pelkonen, Olavi R.; Tolonen, Ari (Frontiers in Pharmacology, 2010)
Liquid chromatography-mass spectrometry (LC/MS) with generic gradient elution for a large number of chemically different compounds is a common approach in drug development, used to acquire a large amount of data in a short time frame for drug candidates. The analysis with non-optimised parameters however may lead to a poor method performance for many compounds, and contains a risk of losing important information. Here, generic electrospray-time-of-flight (ESI-TOF) MS methods in various pH conditions were tested for 55 chemically diverse compounds (10 acids, 25 bases, 17 neutrals and 3 amphoterics), aiming to find best analytical conditions for each compound, for studies of in vitro metabolic properties in liver preparations. The effect of eluent pH and elution gradient strength on chromatographic performance and electrospray MS ionisation efficiency were examined for each compound. The data are evaluated how well the best generic approach could cover the analysis of test compounds and how many compounds would still need completely different analytical conditions after that. Aqueous mobile phase consisting of 0.05% acetic acid and 5 mM ammonium acetate (pH 4.4) showed the best general suitability for the analyses, showing adequate performance for metabolite profiling for 41 out of 55 compounds either in positive or negative ion mode. In positive ion mode, the main limitation of performance in various pH conditions was generally not the lack of ionisation, but rather the poor chromatographic performance (inadequate retention or poor peak shape), suggesting that more emphasis should be put in finding conditions providing best chromatographic performance, rather than highest ionisation properties. However, a single generic approach for a large number of different compounds is not likely to produce good results for all compounds. Preferably, at least two or three different conditions are needed for the coverage of a larger number of structurally diverse compounds.